Integrative modelling coupled with ion mobility mass spectrometry reveals structural features of the clamp loader in complex with single-stranded DNA binding protein - Politis, A; Park, A; Hall, Z; Ruotolo, B; Robinson, C (2013)
DNA polymerase III, a decameric 420-kDa assembly, simultaneously replicates both strands of the chromosome in Escherichia coli. A subassembly of this holoenzyme, the seven-subunit clamp loader complex, is responsible for loading the sliding clamp (β2) onto DNA. Here, we use structural information derived from ion mobility mass spectrometry (IM-MS) to build three-dimensional models of one form of the full clamp loader complex, γ3δδ′ψχ (254 kDa). By probing the interaction between the clamp loader and a single-stranded DNA (ssDNA) binding protein (SSB4) and by identifying two distinct conformational states, with and without ssDNA, we assemble models of ψχ-SSB4 (108 kDa) and the clamp loader-SSB4 (340 kDa) consistent with IM data. A significant increase in measured collision cross-section (~ 10%) of the clamp loader-SSB4 complex upon DNA binding suggests large conformational rearrangements. This DNA bound conformation represents the active state and, along with the presence of ψχ, stabilises the clamp loader-SSB 4 complex. Overall, this study of a large heteromeric complex analysed by IM-MS, coupled with integrative modelling, highlights the potential of such an approach to reveal structural features of previously unknown complexes of high biological importance. © 2013 Elsevier Ltd.